De matadores de mujeres, amantes despechadas y otros sujetos no menos peligrosos: Crímenes pasionales en la nota roja y la literatura porfirianas - Speckman Guerra, Elisa (1998)
As well as political and social models, the Porfirian elites adopted the code of conduct and values ​​in vogue in Europe. According to this scheme, the actions of the individual should originate from rational dictates, instead of obeying needs, instincts and emotions. Thus, for a human being to be considered a "civilized" person, he had to be moderate in his habits (including actions such as speaking, dressing or eating), control the expression of his feelings and, above all, regulate his behavior. impulses and act calmly.